Clinical and molecular characterisation of two siblings with fibrodysplasia ossificans progressiva, from the Colombian Pacific coast (South America) (2015)
Fibrodysplasia ossificans progressiva (FOP, MIM 135 100) is an uncommon genetic disease with a dominant autosomal germline transmission pattern; however, most cases are products of spontaneous individual mutations. It is a disabling condition that affects connective tissue, and it is distinguished by progressive heterotopic ossifications and congenital malformations of the great toes. The case of 2 brothers with progressive osseous deformation, along with ankylosis of the jaw, scoliosis and mental retardation, is presented. Blood samples were taken from each patient identifying in both of them a heterozygote mutation in exon 6 of the gene ACVR1 (c.617G>A p.Arg206His), which diagnoses the 'classic' form of FOP. The current medical treatment of this disease is early detection to avoid trauma and aggravating factors, prophylactic measures against infections and respiratory decline, symptomatic relief and physical therapy. There is currently no cure for the disease. © 2015 BMJ Publishing Group. All rights reserved.